2-(3′-Indolyl)-N-arylthiazole-4-carboxamides: Synthesis and evaluation of antibacterial and anticancer activities. Issue 19 (1st October 2015) - Tantak, Mukund P.; Wang, Jing; Singh, Rajnish Prakash; Kumar, Anil; Shah, Kavita; Kumar, Dalip
Graphical abstract: Abstract: A new series of 2-(3′-indolyl)- N -arylthiazole-4-carboxamides 17a –p has been designed and synthesized. Initial reaction of readily available thioamides 15 with bromopyruvic acid under refluxing conditions produced different thiazole carboxylic acids 16 which upon coupling with arylamines by using EDCI·HCl and HOBt afforded diverse arylthiazole-4-carboxamides 17a –p in 78–87% yields. Antibacterial activity evaluation against Gram-positive and Gram-negative bacterial strains led to compounds 17i –k and 17o as potent and selectively (Gram-negative) antibacterial agents. The cytotoxicity of thiazole carboxamides 17a –p was also evaluated on a panel of human cancer cell lines. Among the tested derivatives, compounds 17i (IC50 = 8.64 μM; HEK293T) and 17l (IC50 = 3.41 μM; HeLa) were identified as the most potent analogues of the series. Preliminary mechanism of action studies of thiazole carboxamide 17i suggested that its cytotoxicity against HeLa cells involves the induction of cell death by apoptosis.